If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(-6 + -4v) + -1v = -5v + -20 (-6 * -6 + -4v * -6) + -1v = -5v + -20 (36 + 24v) + -1v = -5v + -20 Combine like terms: 24v + -1v = 23v 36 + 23v = -5v + -20 Reorder the terms: 36 + 23v = -20 + -5v Solving 36 + 23v = -20 + -5v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '5v' to each side of the equation. 36 + 23v + 5v = -20 + -5v + 5v Combine like terms: 23v + 5v = 28v 36 + 28v = -20 + -5v + 5v Combine like terms: -5v + 5v = 0 36 + 28v = -20 + 0 36 + 28v = -20 Add '-36' to each side of the equation. 36 + -36 + 28v = -20 + -36 Combine like terms: 36 + -36 = 0 0 + 28v = -20 + -36 28v = -20 + -36 Combine like terms: -20 + -36 = -56 28v = -56 Divide each side by '28'. v = -2 Simplifying v = -2
| p+12.5=-7.3 | | 3x+4y-2=8 | | -4(3n-1)=2n+32 | | 8(x-10)= | | ln(3x+2)=2.3 | | 17+0.07x=22+0.05x | | 8m=5m+84 | | Ab-3=cb-2d | | (-2y+8)+2y=8 | | -2+5x=7(x+1)+1 | | 51+y=67 | | b-6=14 | | 6(n-5)-7n=5+4n | | 5x-6=18+2x | | .5x-y=18 | | 14x-20=4x | | 1-6r=-10+5r-6-5 | | 2y+5x=-7 | | 29x+14-17x=62 | | 12a+19b+6c+2c-5b-4a= | | 3(-5b+1)=b+35 | | -x=-6-3y | | 1-4b=11-6b | | An=5n-6 | | 2y-9=18-6x | | x+y-3z=8 | | -3x-10=-16 | | 5x+2y=-7 | | 5x+40*4x-24=0 | | 18p+11q+p-4q-4p= | | -1+6+6n-6n=4n-5n | | 3w^3=27w |